The comparison factors between science and religion based on philosophy science: An exploratory literature study - Trisliatanto, Dimas Agung; Nurdianto, Arif Rahman; Iswati, Sri; Suaedi, Falih; Arbay, Evi Aryati; Tasențe, Tănase; Fahreza, Andre; Putri Nurwiyanto, Nova Sabrina (Technium Social Sciences Journal, 2021)
There is in religion that cannot be answered with the philosophy and science of knowledge but can only be answered by spiritual experience. Religion, philosophy, and science each exist in a separate space but must be integrated into human life. There are three things that become tools for humans to seek the truth, namely philosophy, science, and religion. Even though the purpose of these three aspects is to find the truth, they cannot be categorized as the same thing. This study aimed to identifying the comparison factors between science and religion based on philosophy science. The method used a qualitative approach with exploratory literature study. The results of this study concluded that between science and religion based on philosophy science had a very strong relationship, but there were several factors that differentiate between one another. Although religion and science both design and prepared the future of mankind, religion design was further, abstract, and gave peace of life after death, while science and technology were shorter and more concrete designs to faced life in this world. Science talked about knowledge, while religion defined about belief.